Another Twist: The Abstract/Geometric Shapes as Evocation of the Venezuelan Identity - Marín, Elizabeth (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
Identity and its various fragmentary meanings have resulted in a number of areas of use and emotional forms of acceptance and rejection in modern times. To speak of it in the contemporary world means to give another twist to a theme widely addressed within the artistic representations of the Venezuelan territory, as the expression of a speech metartistico built outside their fields of assemblage and which communicates interminably. The present formulation of Venezuelan art shows the ambiguity of a speech on/in the identity mobilized between the apparently foreign and simulated himself, as a sign of recognition, of their identity formulation; agents with which continually revisit the postulates of a hegemonic plastic in the 50 and 60 of the last century, through abstraction and kinetic, and how it is derivative in a sensitive, ephemeral spaces structural geometry and precarious releases in a volatile structures identity.